Representasi Perundungan pada Film “Bebas” - Syachrany, Muhammad Dzidan; Purwanti, Silviana (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
The phenomenon of bullying is rampant, especially in the educational environment, therefore if no prevention is done, bullying in the educational environment will continue. The rampant cases of bullying have made the social phenomenon raised in a film. One of the Indonesian films that depicts bullying is Bebas. This research aims to find out how the representation of bullying is presented in the film Bebas. The method used in this research is the Roland Barthes semiotic method which divides the meaning of understanding into denotation, connotation, and myth through first level and second level analysis. The results of this study show that based on ten scenes that have been selected according to the type of bullying, the conclusion is obtained: the denotation meaning in the film shows verbal, physical and relational bullying with medium shot, medium long shot and close up image techniques. The connotation meaning is aimed at the differences in social class, power, and peer factors between the perpetrators and victims that make the perpetrators have the desire to bully. The myth in this film is that bullying often occurs to new students who change schools, often perceived as weak.